Theology in the early British and Irish gothic, 1764-1834 - Hirst, Sam (Anthem studies in gothic literature (Anthem Press), 2023)
"Theology in the Early British and Irish Gothic, 1764-1832 seeks to explore the extent to which Early British Gothic writing, c.1760-1830, took distinctive shape in the particular theological and theo-political climate of the late eighteenth and early nineteenth centuries"--